Evaluation of the learning curve and complications in unilateral biportal endoscopic transforaminal lumbar interbody fusion: cumulative sum analysis and risk-adjusted cumulative sum analysis - Guo, Wenlong; Ye, Jingyao; Li, Tong; Yu, Yang; Fan, Xiaohong (Journal of orthopaedic surgery and research, 2024)
To evaluate the learning curve and complications in unilateral biportal endoscopic transforaminal lumbar interbody fusion (ULIF) using the Cumulative Sum (CUSUM) analysis and Risk-adjusted Cumulative Sum (RA-CUSUM) analysis. This study retrospectively analyzed 184 consecutive patients who received ULIF in our hospital, including 104 males and 80 females. CUSUM analysis and RA-CUSUM analysis were used to evaluate the learning curve of ULIF based on the operation time and surgical failure rate, respectively. All postoperative complications were defined as surgical failure. Variables of different phases were compared based on the learning curve. The CUSUM analysis showed the cutoff point for ULIF was 29 cases, and the RA-CUSUM analysis showed the cutoff point for ULIF was 41 cases. Operating time and hospital stay were significantly decreased as the learning curve progressed (P < 0.05). Visual analogue score (VAS) and Oswestry disability index (ODI) at the last follow-up were significantly lower than preoperatively. At the last follow-up, a total of 171 patients reached intervertebral fusion, with a fusion rate of 92.9% (171/184). A total of eleven complications were observed, and RA-CUSUM analysis showed that the incidence of complications in the early phase was 17.07% and in the late phase was 2.6%, with a significant difference (P < 0.05). ULIF is an effective minimally invasive lumbar fusion surgical technique. But a learning curve of at least 29 cases will be required to master ULIF, while 41 cases will be required to achieve a stable surgical success rate.